Property Rights Reform in Philippine Agriculture: Framework for Analysis and Review of Recent Experience - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2000)
This paper constructs a framework for and reviews studies on property rights reforms in the agricultural and natural resources sector. In the case of agrarian reform, several hypotheses are posited: that agrarian reform will increase the rate of capital accumulation of beneficiaries and improve tenurial security, but may have negative impacts on land access, investments of landowners, and efficiency of land use. For the natural resources sector, the implications of open access and promotion of property rights are surveyed for the Philippine case. Overall, the review finds that research work is scanty and not clearly generalizable to the national level, even for such a major and longstanding program as agrarian reform. Future research thrusts are enumerated in terms of the issues and hypotheses identified in this review.
Keywords: 330; property rights; Agrarreform; Sachenrecht; Reform; Agrarstruktur; Philippinen